Polyimide, preparation method thereof and polyester electronic adhesive

Through the imidation reaction of modified polyimide with dianhydride monomer and diamine monomer, the problem of insufficient flame retardant performance and adhesive peeling force of existing flexible copper clad adhesives is solved, and efficient flame retardant modification and adhesive performance is achieved, which is suitable for processes at lower temperatures.

CN119775557AActive Publication Date: 2025-04-08SHANGHAI ZHONGHUA TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411983404.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The flame retardant properties and adhesive peeling power of existing flexible copper clad plate (FCCL) adhesives are insufficient, and the process requirements of polyimide glue are high, requiring high-temperature and high-pressure equipment.

Method used

The modified polyimide is prepared by imidation reaction of dianhydride monomer and diamine monomer, used to modify the polyester or epoxy system, improve its flame retardant properties and adhesive peeling force, and perform the coating process at lower temperatures.

Benefits of technology

The flame retardant performance and adhesive peeling force of polyester electronic glue are significantly improved, meet the existing process needs, and complete drying at lower temperatures, reducing equipment requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222019580000061
    Figure BDA0005222019580000061
  • Figure BDA0005222019580000071
    Figure BDA0005222019580000071
  • Figure BDA0005222019580000081
    Figure BDA0005222019580000081
Patent Text Reader

Abstract

The invention discloses polyimide, a preparation method thereof and polyester electronic glue. Polymeric monomers of the polyimide comprise a dianhydride monomer and a diamine monomer, the dianhydride monomer is selected from one or more of 4, 4 '-(4, 4'-isopropyl diphenoxy) bis (phthalic anhydride), 3, 3 ', 4, 4'-benzophenone tetracarboxylic dianhydride, 4, 4 '-oxydiphthalic anhydride and 2, 3, 3', 4 '-biphenyl tetracarboxylic dianhydride, and the diamine monomer is selected from one or more of 4, 4'-(4, 4 '-isopropyl diphenoxy) bis (phthalic anhydride), 3, 3', 4, 4 '-benzophenone tetracarboxylic dianhydride and 2, 3, 3', 4 '-biphenyl tetracarboxylic dianhydride. The diamine monomer is selected from one or more of dapsone, 1, 3-bis (4 '-aminophenoxy) benzene, 2, 2'-bis [4-(4-aminophenoxy) phenyl] propane, 4, 4 '-bis (3-aminophenoxy) diphenyl sulfone, 1, 3-cyclohexanedimethylamine, 4, 4'-diaminodiphenyl ether, dimer diamine and trimer diamine. The polyimide disclosed by the invention can be used for modifying polyester or an epoxy system, and the flame retardant property and the adhesion stripping force can be greatly improved. And the coating process is volatilized at a lower temperature, and the solvent boiling point of the system is low, so that the requirements of the existing process can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to polyimide, a preparation method thereof and polyester-containing electronic adhesive. Background Art

[0002] At present, the adhesives used in domestic flexible copper clad laminates (FCCL) are mostly epoxy or polyester systems, which generally do not meet the required flame retardant properties and need to add inorganic powder solids (hydroxides) or phosphorus flame retardants, which will cause a decrease in adhesion or electrical properties. The use of polyimide (PI) adhesives often has high requirements for process equipment and requires high temperature and high pressure equipment. Summary of the invention

[0003] In order to solve the problem of single selectivity of polyester electronic adhesive in the prior art, the present invention provides a polyimide, a preparation method thereof and a polyester electronic adhesive. The polyimide of the present invention can modify the polyester or epoxy system, which can greatly improve the flame retardant performance and adhesive peeling force. The coating process evaporates at a relatively low temperature, and the solvent of the system has a low boiling point, which can meet the existing process requirements.

[0004] The invention provides a polyimide, wherein the polymerization monomers thereof include dianhydride monomers and diamine monomers, wherein the dianhydride monomers are selected from one or more of BPADA (4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride)), BTDA (3,3',4,4'-benzophenonetetracarboxylic anhydride), ODPA (4,4'-oxydiphthalic anhydride) and α-BPDA (2,3,3',4'-biphenyltetracarboxylic anhydride), and the diamine monomers are selected from one or more of DDS (dapsone), TPE-R (1,3-bis(4'-aminophenoxy)benzene), BAPP (2,2'-bis[4-(4-aminophenoxyphenyl)]propane), BAPS-M (4,4'-bis(3-aminophenoxy)diphenyl sulfone), 1,3-BAC (1,3-cyclohexanedimethylamine), ODA (4,4'-diaminodiphenyl ether), dimer diamine and trimer diamine.

[0005] In one embodiment, the dianhydride monomers are BPADA and α-BPDA, for example, the molar ratio of BPADA to α-BPDA is 1:1;

[0006] Alternatively, the dianhydride monomers are OPDA and BPADA, for example, the molar ratio of OPDA to BPADA is 1:1.

[0007] In one embodiment, the diamine monomer is Priamine 1075.

[0008] In one embodiment, the molar ratio of the diamine monomer to the dianhydride monomer is (0.7-1.2):1, for example, 0.9:1.

[0009] In one embodiment, the dianhydride monomers are BPADA and α-BPDA, and the molar ratio of BPADA to α-BPDA is 1:1; the diamine monomer is the dimeramine Priamine 1075; and the molar ratio of the diamine monomer to the dianhydride monomer is 0.9:1;

[0010] Alternatively, the dianhydride monomers are OPDA and BPADA, and the molar ratio of OPDA to BPADA is 1:1; the diamine monomer is the dimeramine Priamine 1075; and the molar ratio of the diamine monomer to the dianhydride monomer is 0.9:1.

[0011] The invention provides a method for preparing a polyimide, which comprises the following steps: at 60° C.-150° C., a dianhydride monomer and a diamine monomer undergo imidization reaction to obtain the polyimide; the dianhydride monomer is selected from BPADA (4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride)), BTDA (3,3',4,4'-benzophenonetetracarboxylic dianhydride), ODPA (4,4'-oxydiphthalic anhydride) and α-BPDA (2,3,3',4 The diamine monomer is selected from one or more of DDS (dapsone), TPE-R (1,3-bis(4'-aminophenoxy)benzene), BAPP (2,2'-bis[4-(4-aminophenoxyphenyl)]propane), BAPS-M (4,4'-bis(3-aminophenoxy)diphenyl sulfone), 1,3-BAC (1,3-cyclohexanedimethylamine), ODA (4,4'-diaminodiphenyl ether), dimer diamine and trimer diamine.

[0012] In a certain embodiment, the dianhydride monomer and the diamine monomer participate in the reaction in the form of a solution.

[0013] In a certain embodiment, the solvent of the solution is selected from one or more of ketone solvents, hydrocarbon solvents and ester solvents. The ketone solvent is, for example, cyclobutanone, the hydrocarbon solvent is, for example, aromatic hydrocarbon and / or alkane solvents, the aromatic hydrocarbon solvent is, for example, toluene and / or xylene, and the alkane solvent is, for example, methylcyclohexane; for another example, the solvent of the solution is a mixed solvent of cyclohexanone and methylcyclohexane, and for another example, the mass ratio of cyclohexanone to methylcyclohexane is (6-10):1, and for another example, it is 9:1.

[0014] In a certain embodiment, in the solution of the dianhydride monomer, the mass ratio of the solvent to the dianhydride monomer is (8-12):1. For another example, it is 10:1.

[0015] In one embodiment, in the diamine monomer solution, the mass ratio of the solvent to the diamine monomer is (8-12):1. For another example, it is 10:1.

[0016] In a certain embodiment, the diamine monomer is added to the dianhydride monomer for reaction; for example, the diamine monomer is added to the dianhydride monomer for reaction at 60°C.

[0017] In one embodiment, the dianhydride monomer is as described in any of the previous embodiments.

[0018] In one embodiment, the diamine monomer is as described in any of the previous embodiments.

[0019] The invention provides a polyimide, which is prepared by the above-mentioned method for preparing the polyimide.

[0020] In one embodiment, the polyimide of the present invention is in the form of a soluble solution.

[0021] In a certain embodiment, the polyimide of the present invention can be dissolved in one or more of butanone, cyclohexanone, toluene, xylene, DMF, methylcyclohexane and ethyl acetate.

[0022] The invention provides an application of the polyimide as a modifier in the preparation of a polyester electronic adhesive composition or polyester electronic adhesive.

[0023] In a certain embodiment, the polyimide of the present invention is added to polyester electronic adhesive to improve the flame retardant performance of the system.

[0024] In a certain embodiment, the polyimide of the present invention is added to polyester electronic adhesive to improve the peeling force of the system.

[0025] The present invention provides a polyester electronic adhesive composition, which comprises 90-95 parts by mass of polyester, 250-270 parts by mass of ketone solvent, 0.3-1 parts by mass of polyimide as described in any of the above schemes, 2-5 parts by mass of epoxy resin, 5-10 parts by mass of halogen-free flame retardant and 3-6 parts by mass of isocyanate.

[0026] In a certain embodiment, the polyester is a copolyester, for example, one or more selected from copolyester Vylon 560, copolyester Vylon 600, and copolyester Vylon 290.

[0027] In one embodiment, the ketone solvent is an aliphatic ketone solvent, such as butanone.

[0028] In one embodiment, the epoxy resin is a glycidyl ether epoxy resin, such as a difunctional epoxy resin or a trifunctional epoxy resin, and another example is a difunctional epoxy resin YN-1828 or a trifunctional epoxy resin 304.

[0029] In a certain embodiment, the halogen-free flame retardant is an inorganic flame retardant and / or an organic flame retardant; the inorganic flame retardant is, for example, a hydroxide, and another example is aluminum hydroxide; the organic flame retardant is, for example, HPCTP.

[0030] In one embodiment, the isocyanate is an aromatic isocyanate, such as isocyanate PDMI (polymethylene polyphenylene isocyanate), and another example is isocyanate PM200 (Wanhua).

[0031] In one embodiment, it contains 92 or 93 parts by mass of polyester.

[0032] In one embodiment, the mixture contains 264 parts by mass of a ketone solvent.

[0033] In one embodiment, it contains 0.5 parts by mass of the polyimide as described in any of the previous embodiments.

[0034] In a certain embodiment, it contains 2 or 3 parts by mass of epoxy resin.

[0035] In one embodiment, the composition comprises 10 parts by mass of an inorganic flame retardant.

[0036] In one embodiment, it contains 5 parts by mass of an organic flame retardant.

[0037] In one embodiment, it contains 4 parts by mass of isocyanate.

[0038] In a certain scheme, it includes or is any of the following:

[0039] Scheme 1: 92 parts by weight of copolyester, 264 parts by weight of ketone solvent, 0.5 parts by weight of polyimide as described in any of the previous schemes, 3 parts by weight of epoxy resin, 10 parts by weight of aluminum hydroxide, 5 parts by weight of HPCTP and 4 parts by weight of isocyanate;

[0040] Solution 2: 93 parts by mass of copolyester, 264 parts by mass of ketone solvent, 0.5 parts by mass of polyimide as described in any of the previous solutions, 2 parts by mass of epoxy resin, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate.

[0041] In a certain scheme, it includes or is any of the following:

[0042] Scheme 1: 92 parts by mass of copolyester Vylon 560, 264 parts by mass of ketone solvent, 0.5 parts by mass of polyimide as described in any of the previous schemes, 3 parts by mass of difunctional epoxy resin YN-1828, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate PDMI;

[0043] Solution 2: 92 parts by mass of copolyester Vylon 600, 264 parts by mass of ketone solvent, 0.5 parts by mass of polyimide as described in any of the previous solutions, 3 parts by mass of difunctional epoxy resin YN-1828, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate PDMI;

[0044] Scheme 3: 92 parts by mass of copolyester Vylon 290, 264 parts by mass of ketone solvent, 0.5 parts by mass of polyimide as described in any of the previous schemes, 3 parts by mass of difunctional epoxy resin YN-1828, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate PDMI;

[0045] Scheme 4: 93 parts by mass of copolyester Vylon 560, 264 parts by mass of ketone solvent, 0.5 parts by mass of polyimide as described in any of the previous schemes, 2 parts by mass of trifunctional epoxy resin 304, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate PDMI;

[0046] Scheme 5: 93 parts by mass of copolyester Vylon 600, 264 parts by mass of ketone solvent, 0.5 parts by mass of polyimide as described in any of the previous schemes, 2 parts by mass of trifunctional epoxy resin 304, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate PDMI;

[0047] Scheme 6: 93 parts by mass of copolyester Vylon 290, 264 parts by mass of ketone solvent, 0.5 parts by mass of polyimide as described in any of the previous schemes, 2 parts by mass of trifunctional epoxy resin 304, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate PDMI.

[0048] The present invention provides a method for preparing polyester electronic adhesive, and its raw materials include: a composition for polyester electronic adhesive as described in any of the above schemes.

[0049] In one embodiment, the polyester is dissolved in the ketone solvent and mixed with the polyimide, epoxy resin and halogen-free flame retardant.

[0050] In one embodiment, the polyester is dissolved in the ketone solvent, mixed with the polyimide, epoxy resin and halogen-free flame retardant, ground, mixed with the isocyanate, coated and dried.

[0051] The present invention provides a polyester electronic adhesive, which is prepared from the polyester electronic adhesive composition described in any of the above schemes.

[0052] The present invention provides a polyester electronic adhesive, which is prepared by the preparation method of the polyester electronic adhesive as described in any of the above schemes.

[0053] In a certain embodiment, the flame retardant grade of the polyester electronic adhesive of the present invention is V0, and the test method refers to UL 94.

[0054] In a certain embodiment, the peeling force of the polyester electronic adhesive of the present invention is 2.5-3.0, for example, 2.6, 2.7, 2.8, 2.9 or 3.0, and the test method refers to GB / T 2791.

[0055] In a certain embodiment, the polyester electronic adhesive of the present invention can be preliminarily dried in a drying oven at 80-160°C, and the pressing temperature with the copper foil can be below 200°C.

[0056] The present invention provides a flexible copper-clad laminate, which comprises the polyester electronic adhesive as described in any of the above schemes.

[0057] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0058] The reagents and raw materials used in the present invention are commercially available.

[0059] The positive progress of the present invention is that the polyimide of the present invention can modify the polyester or epoxy system, which can greatly improve the flame retardant performance and adhesive peeling force. The coating process evaporates at a lower temperature, and the solvent of the system has a low boiling point, which can meet the existing process requirements. DETAILED DESCRIPTION

[0060] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0061] The corresponding abbreviations of the compounds in the present invention and the structural formulas of the compounds are shown in the following table.

[0062]

[0063]

[0064]

[0065] Preparation Example 1: Synthesis process of soluble TPI-1 solution:

[0066] First, 29.42g of α-BPDA monomer and 52.05g of BPADA monomer were added to the reactor, and then 767.52g of a mixture of cyclohexanone and methylcyclohexane was added to the reactor, wherein the mass ratio of cyclohexanone to methylcyclohexane was 9:1, and stirred to form a solution or suspension, and the temperature was raised to 60°C. 108.14g of Priamine 1075 was dissolved in 973.30g of a mixture of cyclohexanone and methylcyclohexane, wherein the mass ratio of cyclohexanone to methylcyclohexane was 9:1, and then slowly added to the reactor of the suspension of the above dianhydride, and continued to heat from 60°C to 150°C, reacted for 20 hours, and after the imidization reaction was completed, a soluble TPI-1 solution was obtained, and the concentration of polyimide in the TPI-1 solution was 10%, which was set aside.

[0067] Preparation Example 2: Synthesis process of soluble TPI-2 solution:

[0068] First, 31.02g of ODPA monomer and 52.05g of BPADA monomer were added to the reactor, and then 767.52g of cyclohexanone and methylcyclohexane mixed solution were added to the reactor, wherein the mass ratio of cyclohexanone to methylcyclohexane was 9:1, stirred to form a solution or suspension, and heated to 60°C. 108.14g of Priamine 1075 was dissolved in 973.30g of cyclohexanone and methylcyclohexane mixed solution, wherein the mass ratio of cyclohexanone to methylcyclohexane was 9:1, and then slowly added to the reactor of the suspension of the above dianhydride, and heated to 60°C to 150°C at the same time, reacted for 20 hours, and after the imidization reaction was completed, a soluble TPI-2 solution was obtained, and the concentration of polyimide in the TPI-2 solution was 10%, which was set aside.

[0069] Example 1

[0070] Take 92g of copolyester Vylon 560 and add it to 264g of butanone for dissolution. After Vylon 560 is dissolved, add 3g of YN-1828, 10g of aluminum hydroxide, 5g of HPCTP, and 5g of homemade TPI-1 solution, stir and disperse them thoroughly, and grind them twice with a grinder. Add 4g of isocyanate PDMI before use, stir and mix evenly, and use it up within 48 hours. Use a coating machine to coat the PI film, and then dry it in a segmented drying tunnel. The five-stage drying temperatures are 90℃, 130℃, 170℃, 165℃, and 160℃, respectively. The time in the drying tunnel is 4 to 8min, and finally a 8μm thick adhesive layer is obtained. On a vacuum hot press, the coated PI film is pressed with copper foil. The pressing conditions are: 20MPa, 180℃, 1min. The pressed samples were ripened in an oven at step-by-step heating conditions, with the heating program being: 60°C*2h, 80°C*4h, 100°C*2h, 120*1h, 160*1h, and cooling*1h to obtain fully ripened samples for subsequent testing.

[0071] Example 2

[0072] Take 92g of copolyester Vylon 600 and add it to 264g of butanone for dissolution. After Vylon 560 is dissolved, add 3g of YN-1828, 10g of aluminum hydroxide, 5g of HPCTP, and 5g of homemade TPI-1 solution, stir and disperse them thoroughly, and grind them twice with a grinder. Add 4g of isocyanate PDMI before use, stir and mix evenly, and use it up within 49 hours. Use a coating machine to coat the PI film, and then dry it in a segmented drying tunnel. The five-stage drying temperatures are 90℃, 130℃, 170℃, 165℃, and 160℃, respectively. The time in the drying tunnel is 4 to 8min, and finally a 8μm thick adhesive layer is obtained. On a vacuum hot press, the coated PI film is pressed with copper foil. The pressing conditions are: 20MPa, 180℃, 1min. The pressed samples were ripened in an oven at step-by-step heating conditions, with the heating program being: 60°C*2h, 80°C*4h, 100°C*2h, 120*1h, 160*1h, and cooling*1h to obtain fully ripened samples for subsequent testing.

[0073] Example 3

[0074] Take 92g of copolyester Vylon290 and add it to 264g of butanone for dissolution. After Vylon560 is dissolved, add 3g of YN-1828, 10g of aluminum hydroxide, 5g of HPCTP, and 5g of homemade TPI-1 solution, stir and disperse them thoroughly, and grind them twice with a grinder. Add 4g of isocyanate PDMI before use, stir and mix evenly, and use it up within 50 hours. Use a coating machine to coat the PI film, and then dry it in a segmented drying tunnel. The five-stage drying temperatures are 90℃, 130℃, 170℃, 165℃, and 160℃, respectively. The time in the drying tunnel is 4 to 8min, and finally a 8μm thick adhesive layer is obtained. On a vacuum hot press, the coated PI film is pressed with copper foil. The pressing conditions are: 20MPa, 180℃, 1min. The pressed samples were ripened in an oven at step-by-step heating conditions, with the heating program being: 60°C*2h, 80°C*4h, 100°C*2h, 120*1h, 160*1h, and cooling*1h to obtain fully ripened samples for subsequent testing.

[0075] Example 4

[0076] Take 93g of copolyester Vylon 560 and add it to 264g of butanone for dissolution. After Vylon 560 is dissolved, add 2g of epoxy resin 304, 10g of aluminum hydroxide, 5g of HPCTP, and 5g of homemade TPI-2 solution, stir and disperse them thoroughly, and grind them twice with a grinder. Add 4g of isocyanate PDMI before use, stir and mix evenly, and use it up within 48 hours. Use a coating machine to coat the PI film, and then dry it in a segmented drying tunnel. The five-stage drying temperatures are 90℃, 130℃, 170℃, 165℃, and 160℃, respectively. The time in the drying tunnel is 4 to 8min, and finally a 8μm thick adhesive layer is obtained. On a vacuum hot press, the coated PI film is pressed with copper foil. The pressing conditions are: 20MPa, 180℃, 1min. The pressed samples were ripened in an oven at step-by-step heating conditions, with the heating program being: 60°C*2h, 80°C*4h, 100°C*2h, 120*1h, 160*1h, and cooling*1h to obtain fully ripened samples for subsequent testing.

[0077] Example 5

[0078] Take 93g of copolyester Vylon 600 and add it to 264g of butanone for dissolution. After Vylon 560 is dissolved, add 2g of epoxy resin 304, 10g of aluminum hydroxide, 5g of HPCTP, and 5g of homemade TPI-2 solution, stir and disperse them thoroughly, and grind them twice with a grinder. Add 4g of isocyanate PDMI before use, stir and mix evenly, and use it up within 48 hours. Use a coating machine to coat the PI film, and then dry it in a segmented drying tunnel. The five-stage drying temperatures are 90℃, 130℃, 170℃, 165℃, and 160℃, respectively. The time in the drying tunnel is 4 to 8min, and finally a 8μm thick adhesive layer is obtained. On a vacuum hot press, the coated PI film is pressed with copper foil. The pressing conditions are: 20MPa, 180℃, 1min. The pressed samples were ripened in an oven at step-by-step heating conditions, with the heating program being: 60°C*2h, 80°C*4h, 100°C*2h, 120*1h, 160*1h, and cooling*1h to obtain fully ripened samples for subsequent testing.

[0079] Example 6

[0080] Take 93g of copolyester Vylon 290 and add it to 264g of butanone for dissolution. After Vylon 560 is dissolved, add 2g of epoxy resin 304, 10g of aluminum hydroxide, 5g of HPCTP, and 5g of homemade TPI-2 solution, stir and disperse them thoroughly, and grind them twice with a grinder. Add 4g of isocyanate PDMI before use, stir and mix evenly, and use it up within 48 hours. Use a coating machine to coat the PI film, and then dry it in a segmented drying tunnel. The five-stage drying temperatures are 90℃, 130℃, 170℃, 165℃, and 160℃, respectively. The time in the drying tunnel is 4 to 8min, and finally a 8μm thick adhesive layer is obtained. On a vacuum hot press, the coated PI film is pressed with copper foil. The pressing conditions are: 20MPa, 180℃, 1min. The pressed samples were ripened in an oven at step-by-step heating conditions, with the heating program being: 60°C*2h, 80°C*4h, 100°C*2h, 120*1h, 160*1h, and cooling*1h to obtain fully ripened samples for subsequent testing.

[0081] Comparative Example 1

[0082] Take 97g of copolyester Vylon 560 and add it to 280g of butanone for dissolution. After Vylon 560 is dissolved, add 3g of YN-1828, 15g of aluminum hydroxide, and 7g of HPCTP, stir and disperse them thoroughly, and grind them twice with a grinder. Add 4g of isocyanate PDMI before use, stir and mix evenly, and use it up within 48 hours. Use a coating machine to coat the PI film, and then dry it in a segmented drying tunnel. The five-stage drying temperatures are 90℃, 130℃, 170℃, 165℃, and 160℃, respectively. The time in the drying tunnel is 4 to 8min, and finally a 8μm thick adhesive layer is obtained. On a vacuum hot press, the coated PI film is pressed with copper foil. The pressing conditions are: 20MPa, 180℃, 1min. The pressed samples were ripened in an oven at step-by-step heating conditions, with the heating program being: 60°C*2h, 80°C*4h, 100°C*2h, 120*1h, 160*1h, and cooling*1h to obtain fully ripened samples for subsequent testing.

[0083] Comparative Example 2

[0084] Take 97g of copolyester Vylon 600 and add it to 280g of butanone for dissolution. After Vylon 560 is dissolved, add 3g of YN-1828, 15g of aluminum hydroxide, and 7g of HPCTP, stir and disperse them thoroughly, and grind them twice with a grinder. Add 4g of isocyanate PDMI before use, stir and mix evenly, and use it up within 49 hours. Use a coating machine to coat the PI film, and then dry it in a segmented drying tunnel. The five-stage drying temperatures are 90℃, 130℃, 170℃, 165℃, and 160℃, respectively. The time in the drying tunnel is 4 to 8min, and finally a 8μm thick adhesive layer is obtained. On a vacuum hot press, the coated PI film is pressed with copper foil. The pressing conditions are: 20MPa, 180℃, 1min. The pressed samples were ripened in an oven at step-by-step heating conditions, with the heating program being: 60°C*2h, 80°C*4h, 100°C*2h, 120*1h, 160*1h, and cooling*1h to obtain fully ripened samples for subsequent testing.

[0085] Comparative Example 3

[0086] Take 97g of copolyester Vylon 290 and add it to 280g of butanone for dissolution. After Vylon 560 is dissolved, add 3g of YN-1828, 15g of aluminum hydroxide, and 7g of HPCTP, stir and disperse them thoroughly, and grind them twice with a grinder. Add 4g of isocyanate PDMI before use, stir and mix evenly, and use it up within 50 hours. Use a coating machine to coat the PI film, and then dry it in a segmented drying tunnel. The five-stage drying temperatures are 90℃, 130℃, 170℃, 165℃, and 160℃, respectively. The time in the drying tunnel is 4 to 8min, and finally a 8μm thick adhesive layer is obtained. On a vacuum hot press, the coated PI film is pressed with copper foil. The pressing conditions are: 20MPa, 180℃, 1min. The pressed samples were ripened in an oven at step-by-step heating conditions, with the heating program being: 60°C*2h, 80°C*4h, 100°C*2h, 120*1h, 160*1h, and cooling*1h to obtain fully ripened samples for subsequent testing.

[0087] Comparative Example 4

[0088] Take 98g of copolyester Vylon 560 and add it to 280g of butanone for dissolution. After Vylon 560 is dissolved, add 2g of epoxy resin 304, 15g of aluminum hydroxide, and 7g of HPCTP, stir and disperse them thoroughly, and grind them twice with a grinder. Add 4g of isocyanate PDMI before use, stir and mix evenly, and use it up within 48 hours. Use a coating machine to coat the PI film, and then dry it in a segmented drying tunnel. The five-stage drying temperatures are 90℃, 130℃, 170℃, 165℃, and 160℃, respectively. The time in the drying tunnel is 4 to 8min, and finally a 8μm thick adhesive layer is obtained. On a vacuum hot press, the coated PI film is pressed with copper foil. The pressing conditions are: 20MPa, 180℃, 1min. The pressed samples were ripened in an oven at step-by-step heating conditions, with the heating program being: 60°C*2h, 80°C*4h, 100°C*2h, 120*1h, 160*1h, and cooling*1h to obtain fully ripened samples for subsequent testing.

[0089] Comparative Example 5

[0090] Take 98g of copolyester Vylon 600 and add it to 280g of butanone for dissolution. After Vylon 560 is dissolved, add 3042g of epoxy resin, 15g of aluminum hydroxide, and 7g of HPCTP, stir and disperse them thoroughly, and grind them twice with a grinder. Add 4g of isocyanate PDMI before use, stir and mix evenly, and use it up within 49 hours. Use a coating machine to coat the PI film, and then dry it in a segmented drying tunnel. The five-stage drying temperatures are 90℃, 130℃, 170℃, 165℃, and 160℃, respectively. The time in the drying tunnel is 4 to 8min, and finally a 8μm thick adhesive layer is obtained. On a vacuum hot press, the coated PI film is pressed against the copper foil. The pressing conditions are: 20MPa, 180℃, 1min. The pressed samples were ripened in an oven at step-by-step heating conditions, with the heating program being: 60°C*2h, 80°C*4h, 100°C*2h, 120*1h, 160*1h, and cooling*1h to obtain fully ripened samples for subsequent testing.

[0091] Comparative Example 6

[0092] Take 98g of copolyester Vylon 290 and add it to 280g of butanone for dissolution. After Vylon 560 is dissolved, add 2g of epoxy resin 304, 15g of aluminum hydroxide, and 7g of HPCTP, stir and disperse them thoroughly, and grind them twice with a grinder. Add 4g of isocyanate PDMI before use, stir and mix evenly, and use it up within 50 hours. Use a coating machine to coat the PI film, and then dry it in a segmented drying tunnel. The five-stage drying temperatures are 90℃, 130℃, 170℃, 165℃, and 160℃, respectively. The time in the drying tunnel is 4 to 8min, and finally a 8μm thick adhesive layer is obtained. On a vacuum hot press, the coated PI film is pressed with copper foil. The pressing conditions are: 20MPa, 180℃, 1min. The pressed samples were ripened in an oven at step-by-step heating conditions, with the heating program being: 60°C*2h, 80°C*4h, 100°C*2h, 120*1h, 160*1h, and cooling*1h to obtain fully ripened samples for subsequent testing.

[0093] The above embodiments and effect examples are summarized in the following table:

[0094]

[0095]

[0096]

[0097] Effect test example:

[0098] Drying temperature: Set the five temperature sections of the tunnel oven to 90°C, 130°C, 170°C, 165°C, and 160°C, and set the speed of the conveyor chain so that the PI sample coated with electronic glue takes 6 minutes to pass through the tunnel. When it comes out of the tunnel oven, the solvent is basically evaporated.

[0099] Tg point: refer to GB / T19466.2, specifically: use a differential scanning calorimeter (DSC) instrument, set the scanning temperature range to -30°C ~ 150°C, the heating rate to 5°C / min, obtain a scanning curve, and find the appropriate Tg point on the curve.

[0100] Lamination temperature: Just set the temperature of the lamination roller.

[0101] Peel force: refer to GB / T 2791, specifically:

[0102] Cut the prepared FCCL sample into 5 strips of 200mm*25mm, with the glue coating length greater than 150mm, and test it on the tester. The clamp moves at 100mm / min, and the test length is greater than 125mm. Finally, the average peel force calculated on the curve is the peel force value of the strip. Finally, calculate the average value of the 5 test samples.

[0103] Flame retardant grade: refer to UL 94, specifically:

[0104] 1. Sample preparation: Provide plastic samples that meet the requirements. The samples need to be cut according to the specified size and shape. Generally: length 125mm* width 13mm* thickness 1.5mm.

[0105] 2. Flame exposure: Place the sample vertically on the test stand and use a standard flame source to perform two 10-second combustion tests on the lower end of the sample.

[0106] 3. Observation and recording: Record the time from the start of combustion to the extinction of the sample under the action of the flame. Observe and record whether there are any dripping objects during the combustion process and whether the sample continues to burn.

[0107] 4. Evaluation and determination: Evaluate the flame retardant performance of the sample based on the recorded parameters and the UL94V-0 standard requirements. If the sample meets all the conditions, it is determined to meet the UL94V-0 flame retardant grade requirements.

[0108] Tin furnace test: Set the temperature of the tin furnace to 288℃, cut samples of 2cm*2cm in size, soak them in tin liquid for 20s, take out the samples and observe the surface to see if it is flat and has no protrusions. If there is no delamination, it is qualified and will not explode.

[0109]

Claims

1. A polyimide, characterized in that: The polymerizable monomers include dianhydride monomers and diamine monomers, wherein the dianhydride monomers are selected from one or more of 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride), 3,3',4,4'-benzophenonetetracarboxylic anhydride, 4,4'-oxydiphenylphthalic anhydride and 2,3,3',4'-biphenyltetracarboxylic anhydride, and the diamine monomers are selected from one or more of dapsone, 1,3-bis(4'-aminophenoxy)benzene, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane, 4,4'-bis(3-aminophenoxy)diphenyl sulfone, 1,3-cyclohexanedimethylamine, 4,4'-diaminodiphenyl ether, dimer diamine and trimer diamine.

2. The polyimide according to claim 1, characterized in that It meets one or more of the following conditions: (1) The dianhydride monomers are BPADA and α-BPDA; or, the dianhydride monomers are OPDA and BPADA; (2) The diamine monomer is Priamine 1075; (3) The molar ratio of the diamine monomer to the dianhydride monomer is (0.7-1.2):1; For example, it meets one or more of the following conditions: (1) The molar ratio of BPADA to α-BPDA is 1:1; or, the molar ratio of OPDA to BPADA is 1:1; (2) the molar ratio of the diamine monomer to the dianhydride monomer is 0.9:1; For another example, it meets the following conditions: The dianhydride monomers are BPADA and α-BPDA, and the molar ratio of BPADA to α-BPDA is 1:1; the diamine monomer is the dimeramine Priamine 1075; and the molar ratio of the diamine monomer to the dianhydride monomer is 0.9:1; Alternatively, the dianhydride monomers are OPDA and BPADA, and the molar ratio of OPDA to BPADA is 1:1; the diamine monomer is the dimeramine Priamine 1075; and the molar ratio of the diamine monomer to the dianhydride monomer is 0.9:

1.

3. A method for preparing a polyimide, characterized in that: It includes the following steps: Under the condition of 60°C-150°C, the dianhydride monomer and the diamine monomer undergo imidization reaction to obtain the polyimide; the dianhydride monomer is selected from one or more of 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride), 3,3',4,4'-benzophenonetetracarboxylic anhydride, 4,4'-oxydiphthalic anhydride and 2,3,3',4'-biphenyltetracarboxylic anhydride; the diamine monomer is selected from one or more of dapsone, 1,3-bis(4'-aminophenoxy)benzene, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane, 4,4'-bis(3-aminophenoxy)diphenyl sulfone, 1,3-cyclohexanedimethylamine, 4,4'-diaminodiphenyl ether, dimer diamine and trimer diamine; It may meet one or more of the following conditions: (1) The dianhydride monomer and the diamine monomer participate in the reaction in the form of a solution: (2) adding the diamine monomer to the dianhydride monomer for reaction; for example, adding the diamine monomer to the dianhydride monomer for reaction at 60° C.; (3) The dianhydride monomer as claimed in claim 2; (4) The diamine monomer as claimed in claim 2; For example, it meets one or more of the following conditions: (1) The solvent of the solution is selected from one or more of ketone solvents, hydrocarbon solvents and ester solvents, the ketone solvent is, for example, cyclobutanone, the hydrocarbon solvent is, for example, aromatic hydrocarbon and / or alkane solvents, the aromatic hydrocarbon solvent is, for example, toluene and / or xylene, and the alkane solvent is, for example, methylcyclohexane; For another example, the solvent of the solution is a mixed solvent of cyclohexanone and methylcyclohexane. For another example, the mass ratio of cyclohexanone to methylcyclohexane is (6-10):1, more preferably 9:1; (2) In the solution of the dianhydride monomer, the mass ratio of the solvent to the dianhydride monomer is (8-12):1; for example, 10:1; (3) In the diamine monomer solution, the mass ratio of the solvent to the diamine monomer is (8-12):1; for example, 10:

1.

4. A polyimide prepared by the preparation method according to claim 3.

5. Use of the polyimide according to any one of claims 1 to 2 and 4 as a modifier in the preparation of a polyester electronic adhesive composition or polyester electronic adhesive.

6. A polyester electronic adhesive composition, characterized in that: The invention comprises 90-95 parts by mass of polyester, 250-270 parts by mass of ketone solvent, 0.3-1 parts by mass of the polyimide according to any one of claims 1-2 and 5, 2-5 parts by mass of epoxy resin, 5-10 parts by mass of halogen-free flame retardant and 3-6 parts by mass of isocyanate.

7. The polyester electronic adhesive composition according to claim 6, characterized in that: It meets one or more of the following conditions: (1) The polyester is a copolyester, for example, one or more selected from copolyester Vylon 560, copolyester Vylon 600, and copolyester Vylon 290; (2) The ketone solvent is selected from aliphatic ketone solvents, such as butanone; (3) The epoxy resin is selected from a glycidyl ether type epoxy resin, such as a difunctional epoxy resin or a trifunctional epoxy resin, and another example is a difunctional epoxy resin YN-1828 or a trifunctional epoxy resin 304; (4) The halogen-free flame retardant is an inorganic flame retardant and / or an organic flame retardant; the inorganic flame retardant is, for example, a hydroxide, and another example is aluminum hydroxide, and the organic flame retardant is, for example, HPCTP; (5) The isocyanate is an aromatic isocyanate, such as isocyanate PDMI; For example, it meets one or more of the following conditions: (1) It contains 92 or 93 parts by mass of polyester; (2) it contains 264 parts by mass of ketone solvent; (3) comprising 0.5 parts by mass of the polyimide according to any one of claims 1 to 2 and 4; (4) It contains 2 or 3 parts by mass of epoxy resin; (5) It contains 10 parts by mass of inorganic flame retardant; (6) It contains 5 parts by mass of an organic flame retardant; (7) It contains 4 parts by mass of isocyanate; For another example, it includes or is any of the following solutions: Solution 1: 92 parts by mass of copolyester, 264 parts by mass of ketone solvent, 0.5 parts by mass of the polyimide according to any one of claims 1-2 and 4, 3 parts by mass of epoxy resin, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate; Solution 2: 93 parts by mass of copolyester, 264 parts by mass of ketone solvent, 0.5 parts by mass of the polyimide according to any one of claims 1-2 and 4, 2 parts by mass of epoxy resin, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate; For example, it includes or is any of the following solutions: Solution 1: 92 parts by mass of copolyester Vylon 560, 264 parts by mass of ketone solvent, 0.5 parts by mass of the polyimide as claimed in any one of claims 1 to 2 and 4, 3 parts by mass of difunctional epoxy resin YN-1828, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate PDMI; Solution 2: 92 parts by mass of copolyester Vylon 600, 264 parts by mass of ketone solvent, 0.5 parts by mass of the polyimide as described in any one of claims 1-2 and 4, 3 parts by mass of difunctional epoxy resin YN-1828, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate PDMI; Solution 3: 92 parts by mass of copolyester Vylon 290, 264 parts by mass of ketone solvent, 0.5 parts by mass of the polyimide as described in any one of claims 1-2 and 4, 3 parts by mass of difunctional epoxy resin YN-1828, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate PDMI; Solution 4: 93 parts by mass of copolyester Vylon 560, 264 parts by mass of ketone solvent, 0.5 parts by mass of the polyimide as described in any one of claims 1-2 and 4, 2 parts by mass of trifunctional epoxy resin 304, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate PDMI; Solution 5: 93 parts by mass of copolyester Vylon 600, 264 parts by mass of ketone solvent, 0.5 parts by mass of the polyimide as described in any one of claims 1-2 and 4, 2 parts by mass of trifunctional epoxy resin 304, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate PDMI; Solution 6: 93 parts by mass of copolyester Vylon 290, 264 parts by mass of ketone solvent, 0.5 parts by mass of the polyimide as described in any one of claims 1-2 and 4, 2 parts by mass of trifunctional epoxy resin 304, 10 parts by mass of aluminum hydroxide, 5 parts by mass of HPCTP and 4 parts by mass of isocyanate PDMI.

8. A method for preparing polyester electronic adhesive, characterized in that: The raw materials include the polyester electronic adhesive composition as claimed in claim 6 or 7; For example, it meets one or more of the following conditions: (1) the polyester is dissolved in the ketone solvent and mixed with the polyimide, epoxy resin and halogen-free flame retardant; (2) The polyester is dissolved in the ketone solvent, mixed with the polyimide, epoxy resin and halogen-free flame retardant, ground, mixed with the isocyanate, coated and dried.

9. A polyester electronic adhesive, which is prepared from the polyester electronic adhesive composition according to claim 6 or 7, or prepared by the preparation method according to claim 8; For example, it meets the following conditions: (1) The flame retardant grade of the polyester electronic adhesive is V0; (2) The peeling force of the polyester electronic adhesive is 2.5-3.0, for example, 2.6, 2.7, 2.8, 2.9 or 3.0; (3) The polyester electronic adhesive can be preliminarily dried in a drying oven at 80-160°C, and the pressing temperature with the copper foil can be below 200°C.

10. A flexible copper clad laminate comprising the polyester electronic adhesive according to claim 9.

Citation Information

Patent Citations

  • Polyimide composition

    CN104583274A

  • Polyimide, polyimide-based adhesive, adhesive material, adhesive layer, adhesive sheet, laminated board, wiring board and method of manufacturing the same

    CN107325285A

  • Metal-clad laminate, adhesive sheet, adhesive polyimide resin composition, and circuit board

    JP2018140544A

  • Polyimide and photosensitive resin composition

    JP2018203959A

  • Polyimide, crosslinked polyimide, adhesive film, laminate, coverlay film, copper foil with resin, metal-clad laminate, circuit board and multilayer circuit board

    JP2021147610A